The Ethical Considerations in the Main Practices of the Iranian Legal Medicine Organization: A Qualitative Study - Mohammadnader Sharifi; Masoud Ghadipasha; Amirahmad Shojaei; Saharnaz Nedjat; Roya Rashidpouraie; Hamideh Moosapour; Seyed Mahmood Tabatabaei (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Background: Effective and acceptable practice in Legal Medicine (LM) requires special attention to ethical and professional behaviors. In LM, the importance of practitioners’ compliance with ethical standards is higher. LM covers a wide range of practices, requiring specific ethical considerations. This study aims to identify the ethical principles for considerations in Iranian Legal Medicine Organization (ILMO) from the perspective of experts in LM. Methods: This is an applied and qualitative study using in-depth interviews and conventional content analysis. The study was conducted in three steps: 1) Determination of the main areas of work by reviewing academic texts، surveying 131 experts in this field with a questionnaire. 2) Qualitative Study for determination of ethical considerations of these areas by structured and in-depth interviews with 49 owner’s Forensic and medical ethics experts obtained by purposive sampling and theoretical saturation and analysis of interviews by the conventional approach of content analysis to specify propositions and confirm the reliability of 80% research in coding through the double-coder agreement method. 3) Drafting ethical guidelines by the research group (students، supervisors، and consultants) in the focus group meetings based on the results of the second step. Results: The ethical principles of LM were categorized as general and specific principles according to the perspective of experts in LM. General ethical principles included virtue ethics, professional and ethical behavior, and proper environment and working conditions. The specific ethical principles included six principles related to the entire organization, legal physical examinations, legal mental examinations, dissection rooms and crime scenes, LM laboratories, and LM commissions. Conclusion: Developing and implementing general and specific ethical guidelines for ILMO is recommended. The comprehensive and holistic view of ethical considerations for main practices of LM in Iran provided by this study can be seen as a good taxonomy and a preliminary step to develop local ethical guidelines.